Utilization of Instagram Account @Sipbanchips as a Marketing Medium For Chips Banana Sip In Lumajang - Hardiwahyuni, Chiska; Widodo, Joko; Zulianto, Mukhamad (Economos : Jurnal Ekonomi dan Bisnis, 2023)
The use of social media in business activities can be a new innovation in the world of marketing that is able to change the way of direct marketing to digital marketing. Instagram is one of the social media applications that can be used to market products by utilizing all the features available on Instagram to beautify photos and videos before uploading them. The lack of optimal marketing of MSME products in Lumajang Regency is because business actors only rely on direct marketing through their stores and have not done marketing through social media. This happens because of the lack of knowledge of MSME actors about marketing through social media and the assumption that manual marketing is easier and more familiar than marketing through social media. SIP Banana Chips is a snack product originating from Lumajang Regency which has been successfully marketed through the use of Instagram as a product marketing medium on @sipbanchips account. SIP banana chip products are marketed through Instagram by utilizing several features including Instagram Feed (Upload photos & videos), Instagram Stories, Instagram, Stories Highlights, Captions, Link On Bio, Followers, Comments and Likes, and Hashtags. The results showed that the use of Instagram as a marketing medium can be profitable for MSME players so that they can save costs in marketing.